Pengaruh religiusitas, personalitas, dan pertimbangan pasar kerja terhadap minat mahasiswa Akuntansi berkarir di Lembaga Keuangan Syari’ah - Fitri, Sasliana; Wahyudin, Wahyudin; Farida, Yusriyati Nur (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to find out how religiosity, personality, and labor market considerations influence the interest of accounting students in having careers in Islamic financial institutions. This study uses primary data obtained through questionnaires. To find representative data, the selection of this research sample used purposive sampling, with a sample of 113 respondents. Data analysis used validity and reliability, descriptive statistical analysis, the classical assumption test, multiple regression analysis, and hypothesis testing. This study uses the Theory of Reasoned Action (TRA) and the Theory of Planned Behavior (TPB), both of which are used to study human action where individual desires and unwillingness are based on behavior. TRA and TPB are formed by three factors, namely: individual attitudes, subjective norms, and behavioral control. The results of this study indicate that religiosity, personality, and labor market considerations have a positive and significant effect on the interest of accounting students in having careers in Islamic financial institutions.